Making Non-Financial Information Auditable: AI’s Influence on the Operationalization of Non-Financial Materiality - Heydarova,Firangiz; Jocz,Mateusz (2025)
Abstract Title: Making Non-Financial Information Auditable: AI’s Influence on the Operationalization of Non-Financial Materiality Course: BUSN79 Degree Project: Accounting and Finance Course: BUSN79 Degree Project: Accounting and Finance Authors: Firangiz Heydarova and Mateusz Jocz Supervisor: Liesel Klemcke Examiner: Anders Anell Purpose: The study aims to explore how AI technologies influence the operationalization of materiality in non-financial assurance engagements. It seeks to uncover AI systems' role in addressing materiality challenges and discuss how AI affects professional judgment in this area. Methodology: This study adopts a qualitative research method using an interpretivist approach. Data was collected through semi-structured interviews with six audit professionals specializing in non-financial assurance within the EU, namely in the Nordics. Thematic analysis, informed by Braun and Clarke (2006), and Gioia et al. (2013), was used to analyze the interview data. Theoretical perspectives: The study draws on Power's "Making Things Auditable" framework to understand the influence of AI on the emerging non-financial materiality operationalization. This is supplemented by literature on financial and non-financial materiality, on AI in auditing, and professional judgment. Empirical foundation: Based on interviews with assurance professionals regarding their experiences with non-financial materiality. Conclusions: The non-financial assurance field, especially under CSRD, is evolving with a lack of standard methodologies and increased reliance on professional judgment. AI is found to be used in a supportive role for tasks like identification and review, with potential benefits in efficiency, and lesser to objectivity. The integration of AI does not diminish but increases the importance of professional judgment, particularly for reviewing AI output and interpreting qualitative data. Lastly, non-financial materiality operationalization is found as a negotiated practice influenced by human judgment and control.
Keywords: AI; Artificial Intelligence; Non-Financial Assurance; Materiality; Operationalization; Professional Judgment; Audit; Non-financial reporting